Translation, adaptation and practicability of Nurses' knowledge of high alert medications to the Brazilian culture - Priscila Peruzzo Apolinario; Roberta Cunha Matheus Rodrigues; Juliana Bastoni Silva; Silvia Regina Secoli; Maria Helena de Melo Lima (Universidade Federal de Goias, 2015)
This is a methodological study with the aim to translate, adapt and assess the practicability of parts A and B of the instrument Nurses' knowledge of high-alert medications to the Brazilian culture. The translation and cultural adaptation followed the steps recommended by the international literature. The appointed judges assessed the semantic, idiomatic, conceptual and cultural equivalences; the degree of agreement among the judges was quantified by the Content Validity Index. The translation and back-translation stages were successfully performed and the assessment of the synthesized version by the committee resulted in changes of questions, ensuring the equivalence between the original and the translated versions. The specialists suggested three new questions for the instrument. Some questions were reformulated in the pre-testing stage to improve understanding. The Brazilian version of the instrument obtained satisfactory outcomes in terms of translation, cultural adaptation and practicability, being considered as easily applicable and viable for clinical practice.